Peran Kepala Madrasah dalam Menemukan Solusi “Jalan Tikus” Pemberantasan Korupsi Melalui Sikap Disiplin di Madrasah Tsanawiyah Swasta Islamiyah At-Taqwa Medan Belawan - Nazza Mahira (Adabiyah Islamic Journal, 2023)
located on Cileduk street right next to the KUA Belawan II Office, Medan Belawan District, Medan madya city. Madrasah Tsanawiyah Islamiyah At-Taqwa has its own uniqueness as there is a Socialization Program for planting anti-corruption values taught by teachers to students in learning, especially Civic Education and Islamic Religious Subjects regarding disciplinary attitudes through the direction of the principal as a coach in the program. This study aims first: to describe the role of madrasah heads in finding solutions to the "rat road" of eradicating corruption in Mts Islamiyah At-Taqwa Belawan through a disciplined attitude to realize anti-corruption values. This research uses a qualitative type with Edmund Husserl's phenomenological approach. Data collection techniques with participant observation techniques, in-depth interviews, and documentation. The result of this study is a joint class by realizing the application of anti-corruption values through the role of the head of the madrasa as a coach in finding solutions to the "rat road" eradication and minimizing the culture of corruption in educational institutions. The result of this study is the strategy of the Head of the Madrasah in instilling a disciplined attitude as an effort and solution to the "rat road" in the eradication of corruption which starts simply in the school environment through habituation, exemplary, monthly socialization methods regarding the importance of anti-corruption values for all school residents and directs all students to protect themselves, associations, and the environment from the impacts that will give rise to a culture of corruption from an early age. Keywords: Madrasah, Eradication of Corruption, Discipline